Integration of Eco-Feminism and Islamic Values: A Case Study of Pesantren Ath-Thaariq Garut, West Java - Ahmad Sihabul Millah; Suharko Suharko; Hakimul Ikhwan (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
This paper aims to study the integration of eco-feminism and Islam conducted by women activist of pesantren Ath-Thariq, Garut, West Java, in their attempt to conserve the nature. They are highly concerned with this issue as a response towards environmental crisis in Indonesia, especially in Garut. Additionally, there are only a few Muslimah activists that have so far been involved in such a movement. Against this backdrop, this study portrays the ways and results of the integration of eco-feminism and Islam as conducted by women activists of the respective pesantren. In doing so, this qualitative study employs feminism method. The subject of research includes women activists of pesantren Ath-Tariq. It finds the following. Through ontology, the women activist of the pesantren believe that there is no dualism of human being and nature. They protect, preserve, and love nature with a concept of rahmatan li al-‘ālamīn. Through epistemological approach, they integrate local knowledge and Islam to interact with nature. They also implement the principles of heterogenity, human-nature inter-dependability, and the holiness of nature. They believe that caring for nature is a form of religious piety and an alm. Thus, the novelty of this research is a new model of integration between Islam and eco-femism through ontological and epistemological approaches based on empirical experiences of women. It is hoped that women activists could apply this model in protecting and conserving the environment in other places.